(untitled) (Research, Society and Development, 2022)
With the development of social sciences, from 1980 onwards, research on the social capital present in the relationships of individuals that constitute social networks emerged in the literature. In this scenario, the strength of ties (weak and strong) is highlighted as elements that contribute to the success of networks. The relevance of the research is the need to understand the profile of the literature on the contributions of the themes social capital, weak ties and social networks for sustainability. Thus, it is relevant to analyze publications that study the relationship of social capital, social networks and weak ties with sustainability. The methodology used was a systematic literature review with bibliometric analysis. The study was sourced from the Web of Science and Scopus databases. The study was based on the search for the following terms: "sustainability", "social capital", "weak ties", "social networks", "social capital", "weak ties" and "social networks", which generated a a total of 723 articles, from which a sample of 531 was selected for analysis. The results of this work point to the relationship between sustainability and the themes of social capital, weak ties and social networks, their characteristics and their state of the art.